Symbol

# Calculator search results

Formula
Solve the equation
Graph
$y = 1.5 x - 0.5 x + 7$
$y = 0.3 x$
$x$Intercept
$\left ( - 7 , 0 \right )$
$y$Intercept
$\left ( 0 , 7 \right )$
$x$Intercept
$\left ( 0 , 0 \right )$
$y$Intercept
$\left ( 0 , 0 \right )$
$1.5x-0.5x+7 = 0.3x$
$x = - 10$
 Solve a solution to $x$
$\color{#FF6800}{ 1.5 } \color{#FF6800}{ x } - 0.5 x + 7 = 0.3 x$
 Calculate the multiplication expression 
$\color{#FF6800}{ \dfrac { 3 x } { 2 } } - 0.5 x + 7 = 0.3 x$
$\dfrac { 3 x } { 2 } \color{#FF6800}{ - } \color{#FF6800}{ 0.5 } \color{#FF6800}{ x } + 7 = 0.3 x$
 Calculate the multiplication expression 
$\dfrac { 3 x } { 2 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { x } { 2 } } + 7 = 0.3 x$
$\color{#FF6800}{ \dfrac { 3 x } { 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { x } { 2 } } + 7 = 0.3 x$
 Since the denominator is the same as $2$ , combine the fractions into one 
$\color{#FF6800}{ \dfrac { 3 x - x } { 2 } } + 7 = 0.3 x$
$\dfrac { 3 x - x } { 2 } + \color{#FF6800}{ 7 } = 0.3 x$
 Convert an equation to a fraction using $a=\dfrac{a}{1}$
$\dfrac { 3 x - x } { 2 } + \color{#FF6800}{ \dfrac { 7 } { 1 } } = 0.3 x$
$\color{#FF6800}{ \dfrac { 3 x - x } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 7 } { 1 } } = 0.3 x$
 Write all numerators above the least common denominator 
$\color{#FF6800}{ \dfrac { 3 x - x + 14 } { 2 } } = 0.3 x$
$\dfrac { \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ x } + 14 } { 2 } = 0.3 x$
 Calculate between similar terms 
$\dfrac { \color{#FF6800}{ 2 } \color{#FF6800}{ x } + 14 } { 2 } = 0.3 x$
$\dfrac { 2 x + 14 } { 2 } = \color{#FF6800}{ 0.3 } \color{#FF6800}{ x }$
 Calculate the multiplication expression 
$\dfrac { 2 x + 14 } { 2 } = \color{#FF6800}{ \dfrac { 3 x } { 10 } }$
$\color{#FF6800}{ \dfrac { 2 x + 14 } { 2 } } = \color{#FF6800}{ \dfrac { 3 x } { 10 } }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ 5 } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 14 } \right ) = \color{#FF6800}{ 3 } \color{#FF6800}{ x }$
$\color{#FF6800}{ 5 } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 14 } \right ) = \color{#FF6800}{ 3 } \color{#FF6800}{ x }$
 Organize the expression 
$\color{#FF6800}{ 10 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 70 }$
$\color{#FF6800}{ 10 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = - 70$
 Organize the expression 
$\color{#FF6800}{ 7 } \color{#FF6800}{ x } = - 70$
$\color{#FF6800}{ 7 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 70 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 10 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture